1996
DOI: 10.3168/jds.s0022-0302(96)76451-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraruminal Monensin Capsules on Reproductive Performance and Milk Production of Dairy Cows Fed Pasture

Abstract: Cows from three herds calving in spring that were fed on pasture were paired by herd, production index, predicted calving date, and age. One cow from each pair was allocated randomly to the treatment group and received a controlled-release capsule of monensin 1 mo prior to the start of AI. A random sample of 20 matched pairs of cows was selected within each herd to monitor BW and metabolic parameters. Treated cows produced more fat, protein, and liters of milk per day during the 2nd mo of monensin activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
0
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 10 publications
13
32
0
14
Order By: Relevance
“…However, other studies have not shown milk fat depression following monensin administration (e.g., Lean et al, 1994;Duffield et al, 1999). The milk protein content of monensintreated cows was lower than for control cows, in agreement with Hayes et al (1996), Green et al (1999), and Phipps et al (2000), although other studies (e.g., Ramanzin et al, 1997;Benchaar et al, 2006) have not shown a protein response with monensin.…”
Section: Resultsmentioning
confidence: 53%
“…However, other studies have not shown milk fat depression following monensin administration (e.g., Lean et al, 1994;Duffield et al, 1999). The milk protein content of monensintreated cows was lower than for control cows, in agreement with Hayes et al (1996), Green et al (1999), and Phipps et al (2000), although other studies (e.g., Ramanzin et al, 1997;Benchaar et al, 2006) have not shown a protein response with monensin.…”
Section: Resultsmentioning
confidence: 53%
“…Na literatura, encontram-se trabalhos nos quais se obteve aumento da produção de leite em vacas sob suplementação com esse ionóforo (Hayes et al, 1996;Lean et al, 1996;Fellner, 1997;Beckett et al,1998;Sauer et al, 1998;Van Der Werf et al, 1998), enquanto em outros trabalhos (Baile et al, 1982;Dye et al, 1988;Sauer et al, 1989;Ramanzin et al, 1997;Phipps 1997;Green et al, 1999;Juchem et al, 2004), incluindo este, não houve aumento na produção de leite. Existem inúmeros fatores relacionados a esta diferença da ação da monensina na produção de leite, como raça, quantidade de concentrado oferecido e quantidade e duração da administração do ionóforo (Kennelly & Lien, 1997 Duffield et al (1999), a condição corporal dos animais também pode afetar essa resposta.…”
Section: Resultsunclassified
“…A monensina altera as proporções de ácidos graxos voláteis (AGV) no rúmen, principal fonte de energia dos ruminantes, aumentando a proporção de ácido propiônico e diminuindo a proporção de ácido acético e butírico e a relação acetato/propionato sem alterar a produção total de ácidos graxos voláteis, (Dinius et al, 1976;Jiménez et al,1984;Van Beuklen et al, 1984;Fellner et al,1997), a produção de metano (Kennelly & Lien, 1997) e a degradação ruminal da proteína dietética (Hayes et al, 1996).…”
Section: Introductionunclassified
“…Based on data with dairy cattle, monensin has the potential to increase milk production by 0.41 to 0.75 L d -1 (Hayes et al 1996;Beckett et al 1998). Monensin also can have an effect on milk composition.…”
Section: Mots Clésmentioning
confidence: 99%